The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s12649-019-00615-y
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Treated Fly Ash from Fluidized Bed Combustion of Peat, Wood, and Wastes in Concrete

Abstract: Fly ash generation in fluidized bed combustion (FBC) is a critical issue in many countries due to its disposal is becoming increasingly restricted and expensive. Because of this, there is a demand for applications in which these types of fly ashes could be utilized efficiently. One promising use for FBC fly ashes is as a cement replacement material in mortar and concrete. The current concrete regulations do not allow the use FBC fly ash as a supplementary cementitious material, but it can be expected to be inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…A fact that can foresee a positive contribution of particle size reduction on their reactivity. It is possible that the contribution of BFA to the screed mortars strength The satisfactory results obtained in this work with 17 wt.% OPC substitution by as received BFA, are in agreement with other studies that pointed for 20 wt.% OPC replacement as the maximum recommended level [4,6,19,23,24]. Fořt et al [18] suggested 30 wt.% as maximum OPC replacement level.…”
Section: Screeds Fresh and Hardened State Propertiessupporting
confidence: 91%
See 4 more Smart Citations
“…A fact that can foresee a positive contribution of particle size reduction on their reactivity. It is possible that the contribution of BFA to the screed mortars strength The satisfactory results obtained in this work with 17 wt.% OPC substitution by as received BFA, are in agreement with other studies that pointed for 20 wt.% OPC replacement as the maximum recommended level [4,6,19,23,24]. Fořt et al [18] suggested 30 wt.% as maximum OPC replacement level.…”
Section: Screeds Fresh and Hardened State Propertiessupporting
confidence: 91%
“…The use of BFA1 and BFA2 (as received or pre-treated) as OPC substitute promote, in general, a deterioration of the mechanical properties. The same result was achieved by other authors [4,6,23,24]. The mechanical resistance of the specimens prepared with the as-received ashes is as lower as higher is the ash amount, as reported in previous works [4,6,18,23].…”
Section: Screeds Fresh and Hardened State Propertiessupporting
confidence: 89%
See 3 more Smart Citations